Creatividad, velocidad y eficiencia para la innovación y su impacto en la efectividad organizacional (Creativity, speed and efficiency for innovation and their impact in the organizational effectiveness) - Garza, J. B.; Mendoza Gómez, Joel (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. A model to generate innovation in the context of the Mexican organizations with positive influence in the organizacional effectiveness is proposed theoretically and proven empirically of partial way. The present study determines how five constructs: creativity, speed and the efficiency can mark to the positive difference in the effectiveness of the innovative process in organizations in Mexico and as well their effect in the result of the goals (organizacional effectiveness).